Plant diversity impacts forage mass of pastures established after soybean harvest in integrated crop-livestock system - Damian da Silva, Francine; Yasmin Ramos Rodrigues, Karoline; Inocêncio Anunciação, Sérgio; Gimenes Mota, Lucas; Oliveira Santos, Vivian Ionara; Avelino Cabral, Carlos Eduardo (Scientia Agraria Paranaensis, 2023)
Pasture with multiple species is an option for integrated systems, but it is important that competition between forages does not interfere with the productivity of the pasture and, mainly, of the main grass. Therefore, this study aimed to verify if the Paiaguas palisade grass (Urochloa brizantha cv. Paiaguas) yield is suppressed in systems with multiple forage species established after soybean harvest and, identify if the species used in mixed pasture improves the total forage mass and, grass morphological and bromatological composition. Treatments consisted of species diversity: no diversity (Paiaguas palisade grass in monoculture), low diversity (Paiaguas palisade grass with Vigna unguiculata), medium diversity (Paiaguas palisade grass with Vigna unguiculata and Guizotia abyssinica), and high diversity (Paiaguas palisade grass with Vigna unguiculata, Fagopyrum esculentum, Raphanus sativus, and Stylosanthes capitata e Stylosanthes macrocephala). Pastures were established in March, in succession to soybean, and evaluated in June. There was no reduction in forage mass with increasing diversity, however, there was a reduction in the participation of Paiaguas palisade grass in the forage mass, without changing the morphological composition. The increase in species diversity reduced ash and crude protein levels. The increase in plant diversity in the system does not reduce the total available forage mass, however, it considerably reduces the Paiaguas palisade grass participation in the system, with no morphological change in the grass. The increase in diversity reduced the nutritional quality of the pasture, as there was a reduction in the crude protein content and an increase in neutral detergent fiber.